A EVALUATION OF DEPRESSION PREVALENCE AMONG RELIGIOUS LEADERS IN ANÁPOLIS (CIPEEX, 2026)
ABSTRACT:INTRODUCTION: The tension between grace and human nature has been a recurring subject of analysis throughout religious history. Inspired by the teaching of Jesus, “The good shepherd lays down his life for his sheep” (John 10:11)1, it is relevant to assess the prevalence of depression among religious leaders and to propose strategies for health promotion, prevention, and treatment. OBJECTIVE: To analyze the prevalence of depression and its symptoms in religious leaders, identify risk factors, and examine the correlation between epidemiology, psychotropic drug use, and various variables that may affect depression prevalence. METHODS: This observational, cross-sectional, quantitative, and correlational study was conducted using data obtained through a self-administered online questionnaire (Google Forms) in August 2025. The questionnaire was disseminated via email, WhatsApp, Instagram, and Telegram. RESULTS: Among the 50 participants, 2% (1/50) were classified as having “probable” depression according to the Hospital Anxiety and Depression Scale (HADS), while another 2% (1/50) were identified as “possible” depression. Additionally, 14% (7/50) were undergoing treatment with psychotropic drugs. CONCLUSION: In the studied sample, most religious leaders did not exhibit significant depressive symptoms. However, limitations related to data collection and the refusal of some leaders to participate should be considered. Notably, the unsupervised use of psychotropic drugs was associated with adverse outcomes.
Keywords: Depressão; Psicofármacos; Saúde menta; Líderes religiosos